Novel 6‐hydroxyquinolinone derivatives: Design, synthesis, antimicrobial evaluation, in silico study and toxicity profiling. Issue 22 (26th May 2021) - Saleh, Marwa A.; El‐Badry, Mohamed A.; R. Ezz Eldin, Rogy
Abstract: Infectious diseases of bacteria and fungi have become a major risk to public health because of antibiotic and antifungal resistance. However, the availability of effective antibacterial and antifungal agents is becoming increasingly limited with growing resistance to existing drugs. In response to that, novel agents are critically needed to overcome such resistance. A new series of 6‐hydroxyquinolinone 3, 4, 5a, 5b, 6a and 6b bearing different side chains were synthesized and evaluated as antimicrobials against numbers of bacteria and fungi, using inhibition zone technique. As one of these derivatives, compound 3 was identified as a potent antibacterial and antifungal agent against all tested microorganisms with good minimum inhibitory concentration values comparable to reference drugs. Molecular docking studies were performed on antibacterial and antifungal targets; microbial DNA gyrase B of Staphylococcus aureus (PDB ID: 4URO); N ‐myristoyltransferase of Candida albicans (PDB ID: 1IYK), respectively, to predict the most probable type of interaction at the active site of the target protein in addition to binding affinities and orientations of docked ligands. Additionally, in silico prediction in terms of detailed physicochemical ADME and toxicity profile relating drug‐likeness as well as medicinal chemistry friendliness was performed to all synthesized compounds. The results indicated that a novel 4, 6‐dihydroxyquinolin‐2(1 H )‐one (3) is likely to be a newly synthesized drug candidate, indicating low toxicity in addition to good in silico absorption. In order to pave the way for more logical production of such compounds, structure–activity and toxicity relationships are also discussed. Abstract :